PENGARUH LABA BERSIH, ARUS KAS OPERASI DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Pandu Triatmojo; Kirmizi '; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to examine the effect of Net Profit, Operating Cash Flow and Sales Growth on Dividend Policy in manufacturing companies. The population in this study were all manufacturing company engaged in the Manufacturing Industry in Indonesia Stock Exchange and using the 2011 -2013 financial statements of 142 companies. The sample in this study were all manufacturing companies that meet the criteria numbering as many as 26 companies. The analytical method used in this study was multiple regression analysis. Based on the analysis of data, it can be concluded that: 1) there is no significant influence of Net Profit on Dividend Policy; 2) there is a significant influence of Operating Cash Flow on Dividend Policy; and 3) there is a significant influence of Sales Growth on Dividend Policy. In addition, this study also showed that the influence of variables Net Profit, Operating Cash Flow, and Sales Growth can be explained the model of this equation is 31.4% and the remaining 68.6% is influenced by other factors that are not included in the regression equation.Keywords: Net Profit, Operating Cash Flow, Sales Growth influential and Dividend Policy